Implementation of Regional Regulation No. 8/2017 on Investment in Increasing Regional Investment in Bengkulu Province - Ana Tasia Pase; Sandi Aprianto; M. Arafat Hermana; Venysia Adzaniati (Fakultas Hukum Dehasen, 2023)
This thesis research aims to examine and analyze the implementation of PERDA Number 8 of 2017 concerning Investment in Increasing Regional Investment in Bengkulu Province and to examine and analyze what efforts can be made in optimizing PERDA Number 8 of 2017 concerning Investment in Increasing Regional Investment in Bengkulu Province. The method used is empirical and the results of this study indicate that the implementation of PERDA Number 8 of 2017 concerning Investment in increasing regional investment in Bengkulu Province has not gone well, this is due to several factors including: a. There are still unclear arrangements in PERDA Number 8 of 2017 concerning Investment and there are still several articles that overlap; b. Not yet supported by arrangements that should be outlined by the relevant Pergub; c. Convoluted and unclear flow and changes in rules that can hinder processing and extend investment licensing time; d. Not many human resources who have not mastered the evaluation of investment licensing; e. There is a lack of understanding of the evaluation of investment licensing. There are not many human resources who have not mastered the evaluation and licensing process, especially in the field of mining and transportation of mining products. The efforts made by the government in optimizing PERDA Number 8 of 2017 concerning Investment in increasing regional investment in Bengkulu Province have not run optimally and optimally, this is due to two factors including: internal factors and external factors.